Development of augmented reality-based learning media for health material in physical education, sports and health - Iskandar; Rustanto, Heri (Citius : Jurnal Pendidikan Jasmani, Olahraga, dan Kesehatan, 2025)
This study aimed to develop an Augmented Reality (AR)-based learning medium for health topics within Physical Education (PE) subjects at the vocational high school level. The research employed the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation phases. Data were collected through expert validation, teacher assessments, and student response questionnaires during limited and large-scale trials. The validation involved media experts and PE teachers to assess the feasibility and quality of the developed AR media, while students participated in testing to evaluate usability and engagement. The results indicated that the media expert validation obtained an average score of 3.78 (very good), and the PE teachers’ assessment reached 3.81 (very good). Student responses in both limited and large-scale trials showed an overall mean score of 3.72 (good), with the highest aspect being media display and design (3.76) and the lowest being content comprehension (3.68). These findings demonstrate that the AR-based media is feasible, effective, and engaging for use in health education within PE, enabling students to visualize and understand the structure and function of human organs and the effects of physical activity in a more concrete and interactive way. Conclusion health-based Augmented Reality (AR) learning media has the potential to increase the meaningfulness of physical education learning through interactive visualization of Health Concepts. Further research needs to assess the effectiveness, expansion of content, technology integration, and sustainability of the application of AR media.